Vpliv učinka poznanstva in sosedstva na volilno vedenje v volilnem okraju Tolmin - Červ, Alen (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2015)
This paper discusses the impact of friends-and-neighbours effect on results of Slovenian parliamentary elections in 2008 and 2011. Its impact on electoral behaviour has been verified by statistical and cartographic analyses of election results in the Tolmin electoral district. Some cases with weak or moderate impact of analysed phenomena were proven, while spatial distribution of candidates support signalled the differences between urban and rural areas and impact of local specifics (neighbourhood rivalry, gravitation hinterland, career position of candidates) on electoral behaviour.
Keywords: election; politična geografija; Tolmin; volilci; volitve; vplivi